Past, Present and Future of Urology in Pakistan - Manzoor Hussain (Journal of the Pakistan Medical Association, 2021)
There is little published literature on urologic diseases before 1947 from areas now constituting Pakistan. From 1947 to 1970s, urology was part of surgery practiced by general surgeons except for two urology units in 1960s. The real take off of urology began with introduction of transurethral resection of prostate in 1980s, ushering the era of endourology; the second era of which began with ureteroscopy along with extracorporeal shockwave lithotripsy in 1987-1989, percutaneous nephrolithotomy in 1992 and introduction of percutaneous nephrostomy in 1997. Renal transplantation was started in 1979 and currently, there are 19 renal transplant centres. At present, there are 11 specialized kidney centers in the country. Urology has undergone marked metamorphosis during the new millennium with many sub-specialities. Over past few decades, the classical surgical training has shifted toward adaptation of surgical simulation labs. Continuous...